Wireless system for temperature and relative humidity in oil palm tissue culture laboratory / Nur Liyana Ridzuan - Ridzuan, Nur Liyana (2010)
To increase our production of palm oil, the Malaysian Palm Oil Board (MPOB) had adapted the tissue culture technique. This technique was conducted inside the specific laboratory and required frequent monitoring sessions to maintain its crucial parameters in good conditions. To overcome this situation, the wireless monitoring system is developed to reduce the conscripting of manpower monitoring session by using the SHTll sensor to produce the output data for both temperature and relative humidity parameters with direct utilization of the XBee antennas for transmitting and receiving the data in wireless form. The PIC16F877A microcontroller systems are being used to connect the SHTll sensor and XBee antenna as the transmitter part and also connect the XBee antenna and LCD module as the receiver part to display the data measured. This system is developed for upgrading the previous wired monitoring system and overcome the manpower consumption for monitoring session to improve the global standard for the oil palm tissue culture technique.